The Development and Evaluation of an Electronic Health Record Efficiency Workshop for Providers - Scott, Kara; Hathaway, Elizabeth; Sharp, Karen; Smailes, Paula (Applied Clinical Informatics, 2020)
Background The electronic health record (EHR) has historically been known to be a source of stress and dissatisfaction, leading to reduced efficiency and productivity for providers. This issue is complicated by constant changes in EHRs that are necessary to keep systems current with evolving functionality. Knowing the existence of this problem, an evidenced-based solution, known as an efficiency workshop, was developed by our information technology training and optimization team for providers as a means of ongoing professional development.Objectives The objectives of this project were to identify EHR optimization needs for providers in various clinical departments and improve their EHR satisfaction. The development of a program focused on provider efficiency tools and personalization was key and, once piloted, how to measure program success.Methods Efficiency workshops comprised members of the IT training team who set up on site training sessions during reserved time with providers during departmental meetings. Sessions focused on reviewing EHR efficiency tools using demonstration of existing system functionality. Participating providers were given continuing medical education (CME) credits upon completion of evaluations used as a quality improvement tool for the program.Results Descriptive results showed that providers were satisfied with this method of EHR instruction. Subjective feedback yielded positive themes such as informative, well done, organized, and helpful.Conclusion This initiative began as a pilot program and successfully expanded across clinical departments at our academic medical center. Future plans are to sustain and further invest in this program by using EHR reporting features to further customize these sessions and evaluate impact on system use.
Keywords: physician; efficiency; satisfaction; training; education